Reticular Cu2O / TiO2 composite p-n type heterojunction photoelectric catalytic material as well as preparation method and application thereof

By depositing Cu2O on the TiO2 nanotube array to form a mesh Cu2O/TiO2 composite p-n-type heterojunction, the problem of low photoelectro-catalytic efficiency of pure TiO2 is solved, and efficient photoelectrocatalytic production of hydrogen is achieved, and the efficiency is increased to 91%.

CN119243224APending Publication Date: 2025-01-03GUANGXI NORMAL UNIV
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202410959380.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-07-17
Publication Date
2025-01-03

AI Technical Summary

Technical Problem

In the prior art, the photoelectric conversion efficiency of pure TiO2 is low in photoelectric catalytic production of hydrogen, and it is difficult to have both photocatalytic and electrocatalytic properties.

Method used

Cu2O is deposited on TiO2 nanotube array by double electrode oxidation and electrochemical deposition method, and the network Cu2O/TiO2 composite p-n-type heterojunction photoelectro-catalytic material is prepared to widen the absorption of TiO2 in the visible light area and promote photogenesis and current-carrying The separation and transmission of the cells inhibit the recombination of photogenerated electrons and holes.

Benefits of technology

It significantly improves the efficiency of photoelectric catalytic hydrogen production, with a maximum efficiency of up to 91%, and provides safe, cheap and non-toxic new energy materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119243224A_ABST
    Figure CN119243224A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of photoelectrocatalytic materials, and particularly relates to a reticular Cu2O / TiO2 composite p-n type heterojunction photoelectrocatalytic material as well as a preparation method and application thereof. The preparation method comprises the following steps: firstly, adopting a crisscrossed titanium mesh as a substrate, preparing a mesh-shaped TiO2 nanotube array through a dual-electrode oxidation method, and then loading p-type semiconductor Cu2O onto a wide-band-gap n-type semiconductor TiO2 nanotube array through an electrochemical deposition method, so as to prepare the mesh-shaped Cu2O / TiO2 composite p-n type heterojunction photoelectric catalytic material. Compared with a TiO2 material, when the material is used as a photoelectrocatalysis material to prepare hydrogen, the light absorption band edge of TiO2 is widened, the light energy utilization rate of TiO2 is improved, the performance of TiO2 in the aspect of photoelectrocatalysis hydrogen preparation is greatly improved, and the material is suitable for photoelectrocatalysis hydrogen preparation and belongs to the fields of chemical materials, new energy, environment and the like. The problem that the conversion efficiency is low when hydrogen is prepared through pure TiO2 photoelectrocatalysis is solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of photoelectrocatalytic materials and particularly relates to a mesh Cu 2 O / TiO 2 Composite pn-type heterojunction photoelectrocatalytic material and its preparation method and application. Background Art

[0002] With the continuous development of modern society, environmental pollution, energy shortage and ecological damage caused by fossil fuels are becoming more and more serious. Therefore, it is urgent to find and utilize new environmentally friendly renewable energy and fuel materials. Hydrogen, as an environmentally friendly green new energy, has been widely valued.

[0003] Electrocatalytic (EC) hydrogen production is a technology that uses an external bias to electrolyze water to produce hydrogen. It has the advantages of simple operation, high product purity, safe and reliable production technology, and automatic control. Photocatalytic (PC) hydrogen production technology uses solar energy to produce hydrogen under the condition of a photosensitive catalyst. It has low operating costs and is a renewable hydrogen production method. Photoelectrocatalytic (PEC) hydrogen production combines the advantages of photocatalysis and electrocatalytic hydrogen production technology by applying an external bias and light energy at the same time. In the photoelectrocatalytic hydrogen evolution reaction, the electrode material is an important factor affecting the efficiency of photoelectrocatalytic hydrogen production. At present, pure TiO 2 The problem of low photoelectric conversion efficiency in the photoelectrocatalytic production of hydrogen is solved.

[0004] Developing and researching electrode materials that have both photocatalytic and electrocatalytic hydrogen evolution properties, thereby improving hydrogen production efficiency, meets the needs of sustainable development strategies and is of great significance to the future development and utilization of hydrogen energy. Summary of the invention

[0005] One of the purposes of the present invention is to solve the problem of pure TiO 2 The disadvantage of low photoelectric conversion efficiency in the photoelectrocatalytic production of hydrogen is provided by providing a mesh Cu 2 O / TiO 2 A method for preparing a composite pn-type heterojunction photoelectric catalytic material, the method using a double electrode oxidation method and an electrochemical deposition method to 2 O deposition onto TiO 2 The Cu nanotube array was prepared on the titanium mesh. 2 O / TiO 2 Composite pn-type heterojunction photoelectrocatalytic material. Improves the performance in photoelectrocatalytic preparation of new energy materials, especially in the production of hydrogen.

[0006] To achieve the above purpose, the present invention adopts the following technical solution: a mesh Cu 2 O / TiO2 A method for preparing a composite pn-type heterojunction photoelectrocatalytic material comprises the following steps:

[0007] S1. Using ethylene glycol as solvent, add pure water and ammonium fluoride in sequence, and stir evenly to prepare an anodic oxidation electrolyte;

[0008] S2, using a double electrode system, with 80-100 mesh titanium mesh as anode and copper plate as cathode, applying a constant voltage for oxidation to obtain a mesh titanium dioxide nanotube array;

[0009] S3, add copper sulfate pentahydrate to pure water at a concentration of 4-10 g / 200 ml, adjust the pH to 8-10, and continue stirring for 5-12 hours to obtain an alkaline copper sulfate pentahydrate electrolyte;

[0010] S4, using a three-electrode system, immersing the meshed titanium dioxide nanotube array obtained in step S2 in an alkaline copper sulfate pentahydrate electrolyte as a working electrode, soaking for 5-20 minutes until the electrode environment is stable, applying a working voltage of 0.5-1.5V, and obtaining a meshed Cu with a loading of 0.1-0.6C according to the deposited charge displayed by the electrochemical workstation. 2 O / TiO 2 Composite pn-type heterojunction photoelectrocatalytic materials.

[0011] As a mesh Cu 2 O / TiO 2 Further improvement of the preparation method of composite pn-type heterojunction photoelectrocatalytic materials:

[0012] Preferably, the volume of ethylene glycol in the electrolyte of step S1 is 1000 ml, the volume of pure water is 8.75-17.5 ml, and the mass of ammonium fluoride is 2-4 g.

[0013] Preferably, in the electrolyte of step S1, the volume of ethylene glycol is 1000 ml, the volume of pure water is 17.5 ml, and the mass of ammonium fluoride is 4 g.

[0014] Preferably, in step S2, a constant voltage of 10-80 V is applied, and the oxidation time is 0.5-5 h.

[0015] Preferably, in step S2, a constant voltage of 60 V is applied and the oxidation time is 1 h.

[0016] Preferably, copper sulfate pentahydrate is added to pure water in step S3 at a concentration of 5 g / 200 ml.

[0017] Preferably, in step S4, a working voltage of 0.5 V is applied to obtain a mesh Cu with a loading of 0.3C. 2 O / TiO 2 Composite pn-type heterojunction photoelectrocatalytic materials.

[0018] Preferably, in step S4, the counter electrode of the three-electrode system is a platinum sheet, and the reference electrode is a saturated silver chloride electrode.

[0019] The second object of the present invention is to provide a mesh Cu as described in any one of the above 2 O / TiO 2 Preparation method of composite pn type heterojunction photoelectrocatalytic material prepared by mesh Cu 2 O / TiO 2 Composite pn-type heterojunction photoelectrocatalytic materials.

[0020] The third object of the present invention is to provide a mesh Cu 2 O / TiO 2 Application of composite pn-type heterojunction photoelectrocatalytic materials in photoelectrocatalytic production of hydrogen.

[0021] Compared with the prior art, the present invention has the following beneficial effects:

[0022] 1) The present invention provides a mesh Cu 2 O / TiO 2 Preparation method of composite pn-type heterojunction photoelectrocatalytic material. First, a criss-cross titanium mesh is used as a substrate, and a mesh TiO 2 The nanotube array has ultraviolet light absorption properties, and then the p-type semiconductor Cu is deposited on it by electrochemical deposition. 2 O loading into wide-bandgap n-type semiconductor TiO 2 Nanotube arrays widen the TiO 2 Absorption in the visible light region promotes the separation and transmission of photogenerated carriers, inhibits the recombination of photogenerated electrons and holes, and improves the light utilization rate and photoelectrocatalytic efficiency of the material in the photoelectrocatalytic production of hydrogen. 2 Nanotube array loaded with p-type semiconductor Cu 2 O nanoparticles are constructed into a pn-type heterojunction, which can broaden the absorption spectrum of the photoelectrode and enhance the TiO 2 Absorption in the visible light region promotes the separation and transmission of photogenerated carriers, inhibits the recombination of photogenerated electrons and holes, enhances the separation and transfer capabilities of photogenerated electrons and holes, and improves photoelectrocatalytic performance.

[0023] 2) The mesh Cu provided by the present invention 2 O / TiO 2The raw materials for preparing composite pn-type heterojunction photoelectrocatalytic materials are simple and easy to obtain, non-toxic and harmless, safe and cheap, and the preparation method is simple. It provides a new photoelectrocatalytic material for photoelectrocatalytic production of hydrogen and has good application prospects. Especially in the field of photoelectrocatalysis, it is suitable for photoelectrocatalytic hydrogen production, belonging to the fields of chemical materials, new energy, and environment. When used for photoelectrocatalytic production of hydrogen, compared with TiO 2 In terms of the addition of TiO 2 The absorption in the visible light range and the utilization rate of visible light are more conducive to the separation of photogenerated electrons and holes, which greatly improves the TiO 2 The efficiency of photoelectrocatalytic hydrogen production can reach up to 91%. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 (a) is the TiO prepared in Example 1 of the present invention. 2 SEM images of the photoelectrode at magnifications of 400X and 2500X; (b) is the Cu prepared in Example 1 of the present invention. 2 O / TiO 2 SEM images of the photoelectrode at magnifications of 10000X and 40000X; (c) is the Cu prepared in Example 1 of the present invention 2 O / TiO 2 Transmission electron microscope TEM image of the photoelectrode; (d) is the Cu prepared in Example 1 of the present invention 2 O / TiO 2 Elemental scan of the photoelectrode.

[0025] Figure 2 (a) is TiO prepared in Example 1-2 of the present invention. 2 Photoelectrode and different Cu loadings 2 O / TiO 2 X-ray diffraction spectrum XRD diagram of the photoelectrode; (b) is the TiO prepared in Example 1-2 of the present invention 2 Photoelectrode and Cu 2 O / TiO 2 Raman spectrum of the photoelectrode.

[0026] Figure 3 (a)-(d) are Cu prepared in Example 1 2 O / TiO 2 X-ray photoelectron spectroscopy XPS diagram of the photoelectrode.

[0027] Figure 4 The TiO prepared in Example 1 2 Photoelectrode and Cu 2 O / TiO 2 UV-visible diffuse reflectance absorption spectrum (a) and Tauc function diagram (b) of the photoelectrode.

[0028] Figure 5 (a)-(c) are TiO 2 Photoelectrode (a), Cu 2 O photoelectrode (b) and Cu 2 O / TiO 2 Mott-Schottky curve MS diagram of the photoelectrode (c).

[0029] Figure 6 For different loading amounts of Cu in Examples 1-2 2 O / TiO 2 Hydrogen production yield of the photoelectrode (a), hydrogen production Faraday efficiency (b), photocurrent response (c) and EIS (d).

[0030] Figure 7 (a)-(j) are TiO prepared at different oxidation times in Examples 1 and 3, respectively. 2 SEM morphology of the photoelectrode, the oxidation time is 0.5, 1.0h, 1.5h, 2.0h, 2.5h, 3.0h, 3.5h, 4.0h, 4.5h and 5.0h.

[0031] Figure 8 Cu prepared at different oxidation times in Examples 1 and 3 2 O / TiO 2 Hydrogen production yield of the photoelectrode (a), hydrogen production Faraday efficiency (b), photocurrent response (c) and EIS (d).

[0032] Fig. 9 The Cu prepared under different applied voltages in Example 4 2 O / TiO 2 Hydrogen production yield of the photoelectrode (a) and Faraday efficiency of hydrogen production (b). DETAILED DESCRIPTION

[0033] In order to make the purpose, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in the field without making creative work are within the scope of protection of the present invention.

[0034] Example 1

[0035] This embodiment provides a mesh Cu 2 O / TiO 2 The preparation method of the composite pn-type heterojunction photoelectrocatalytic material specifically comprises the following steps:

[0036] S1. Using 1000 ml of ethylene glycol as solvent, add 17.5 ml of pure water and 4 g of ammonium fluoride in sequence, and stir for 12 hours to obtain an anodic oxidation electrolyte;

[0037] S2, using a double electrode system, with a 100-mesh titanium mesh as the anode and a copper plate as the cathode, applying a voltage of 60 V, oxidizing in an anodic oxidation electrolyte for 1 h, to obtain a mesh-like titanium dioxide nanotube array;

[0038] S3, add 5g of copper sulfate pentahydrate to 200ml of pure water, stir evenly, adjust the pH of the solution to 9 with 5M sodium hydroxide solution, and continue stirring for 12h to obtain an alkaline copper sulfate pentahydrate electrolyte;

[0039] S4, using a three-electrode system, immersing the meshed titanium dioxide nanotube array obtained in step S2 in an alkaline copper sulfate pentahydrate electrolyte as a working electrode, soaking for 10 minutes until the electrode environment is stable, applying a working voltage of 0.5V, and obtaining a meshed Cu with a loading of 0.3C according to the deposited charge displayed by the electrochemical workstation. 2 O / TiO 2 Composite pn-type heterojunction photoelectrocatalytic material, denoted as CT-1h-0.3C.

[0040] Example 2

[0041] As a control example of Example 1, the deposited charge amount 0.3C in step S4 was modified to 0.1C, 0.2C, 0.4C, 0.5C and 0.6C in sequence, and the other steps were the same as those in Example 2; finally, a mesh Cu 2 O / TiO 2 The composite pn-type heterojunction photoelectrocatalytic materials are respectively recorded as CT-1h-0.1C, CT-1h-0.2C, CT-1h-0.4C, CT-1h-0.5C, and CT-1h-0.6C.

[0042] A self-made H-type electrolytic cell was used to prepare TiO 2 Nanotube arrays (TiO 2 Photoelectrode) or the mesh Cu prepared in step S4 2 O / TiO 2 Composite pn-type heterojunction photoelectrocatalytic material (Cu 2 O / TiO 2 The photoelectrode was used as the working electrode, the platinum sheet was used as the negative electrode, and the saturated silver chloride electrode was used as the reference electrode for photoelectrocatalytic hydrogen production. The hydrogen production electrolyte was 0.1 M Na 2 SO 4 Electrolyte, test the photoelectrochemical performance of different electrodes.

[0043] A self-made H-type electrolytic cell was used to prepare TiO 2 Nanotube arrays (TiO 2 Photoelectrode) or the mesh Cu prepared in step S4 2 O / TiO 2 Composite pn-type heterojunction photoelectrocatalytic material (Cu 2 O / TiO 2 The photoelectrode was used as the working electrode, the platinum sheet was used as the negative electrode, and the saturated calomel electrode was used as the reference electrode for photoelectrocatalytic hydrogen production. The hydrogen production electrolyte was 0.5 M Na 2 SO 4 Electrolyte, test the photoelectrocatalytic performance of different electrodes.

[0044] Figure 1 (a) is the TiO prepared in step S1 of Example 1 2 Scanning electron microscope (SEM) images of the photoelectrode at 400X and 2500X magnifications. Figure 1 (a) shows that the TiO 2 The photoelectrode has a 360° cylindrical ring-shaped high specific surface area morphology, a smooth surface, close contact with the substrate, and good adhesion; Figure 1 (b) is a scanning electron microscope (SEM) image of the CT-1h-0.3C photoelectrode prepared in step S4 of Example 1 at magnifications of 10000X and 40000X, from which it can be clearly observed that 2 The nanotube array is loaded with Cu 2 O nanoparticles; Figure 1 (c) is a transmission electron microscope (TEM) image of the CT-1h-0.3C photoelectrode prepared in step S4 of Example 1, from which it can be found that the lattice fringe width of TiO 2 (101) crystal plane and 0.24nm Cu 2 O(111) crystal plane; Figure 1 (d) is the element distribution diagram of the CT-1h-0.3C photoelectrode prepared in step S4 of Example 1, showing that Cu 2 O / TiO 2 The photoelectrode is composed of Ti, O and Cu elements without other impurities.

[0045] Figure 2 (a) TiO prepared in Example 1-2 of the present invention 2 Photoelectrode and different Cu loadings 2 O / TiO 2 X-ray diffraction pattern of the photoelectrode. TiO 2 The XRD data show that the TiO 2It is a mixed crystal phase of rutile and anatase with high crystallinity. The XRD image of CT-1h-0.3C photoelectrode shows an obvious diffraction peak at 35.9°, which belongs to Cu 2 O's (111) crystal plane. Figure 2 (b) TiO prepared in Example 1-2 of the present invention 2 Photoelectrode and Cu 2 O / TiO 2 Raman spectrum of the photoelectrode. From it, we can observe TiO 2 The characteristic peaks of -1 Cu 2 O characteristic peak. This result proves that the highly crystalline CT-1h-0.3C composite pn-type heterojunction network photoelectrode was successfully prepared.

[0046] Figure 3 (a)-(d) are Cu prepared in Example 1 2 O / TiO 2 X-ray photoelectron spectroscopy (XPS) of the photoelectrode reveals the surface composition and element oxidation state of the CT-1h-0.3C photoelectrode. XPS analysis confirmed that FeS 2 / TiO 2 The sample contains Ti, O, Fe and S elements, which is completely consistent with the element scanning results. 3 / 2 and Ti2p 1 / 2 are located at 458.18 eV and 463.88 eV, respectively, which indicates that the main state of the Ti element is Ti 4+ .TiO 2 The O1s peak at 529.38 eV in the sample can be attributed to the Ti-O peak and the Cu-O peak. The XPS curve of Cu2p shows Cu + Cu2p at 932.08 eV 3 / 2 and Cu2p at 951.90 eV 1 / 2 , Cu 2+ Cu2p at 933.98eV 3 / 2 and Cu2p at 953.78 eV 1 / 2 This is mainly because the sample is prone to oxidation when exposed to air.

[0047] Figure 4 (a) is the TiO prepared in Example 1 2 UV-visible diffuse reflectance absorption spectra of photoelectrode and CT-1h-0.3C. TiO 2 The photoelectrode absorbs light weakly in the visible light region until the absorption spectrum begins to rise sharply in the ultraviolet band below 380nm, indicating that TiO 2The intrinsic light absorption of TiO 2 It has strong absorption in the ultraviolet region, but weak absorption in the visible region. 2 After being composited with CuO nanoparticles, CT-1h-0.3C began to show obvious light absorption in the near-infrared region of 509.5nm, which shows that the light absorption of CT-1h-0.3C photoelectrode in the visible light band is mainly due to CuO nanoparticles. 2 ODone. Figure 4 (b) Band gap diagram obtained by using Tauc function calculation for the linear absorption region of the photoelectrode, and the TiO 2 The corresponding band gap widths of CT-1h-0.3C are 3.26eV and 2.44eV respectively. 2 After O forms a composite semiconductor, the wide-gap TiO 2 The band gap width of the semiconductor is reduced, and the light absorption performance is greatly improved, which increases the light absorption of the semiconductor in the visible light region.

[0048] The Mott-Schottky method was used to determine the band structure of the CT-1h-0.3C photoelectrode heterojunction. Figure 5 (a)-(c) are TiO 2 Photoelectrode (a), Cu 2 O photoelectrode (b) and Cu 2 O / TiO 2 Mott-Schottky curve MS diagram of the photoelectrode (c). Figure 5 (a) Pure TiO 2 A positive slope was observed in the MS graph, indicating that TiO 2 It is an n-type semiconductor. In contrast, pure Cu 2 The MS graph of O shows a negative slope, indicating that it has the typical characteristics of a p-type semiconductor ( Figure 5 (b)). The MS pattern of CT-1h-0.3C shows an inverted "U" shape ( Figure 5 (c)), indicating that TiO 2 and Cu 2 O forms a pn heterojunction, which is beneficial to the separation of photogenerated charge carriers. 2 O / TiO 2 The hydrogen production graph of the photoelectrode (a), the Faraday efficiency graph of hydrogen production (b), the photocurrent response graph (c) and the EIS graph (d). Figure 6 (a) shows the different loadings of Cu 2 O / TiO 2 The change of hydrogen production of the photoelectrode after continuous irradiation of UV-visible light for 5 hours. Obviously, compared with pure TiO 2 Compared with the photoelectrode, the Cu 2O composite photoelectrode has increased hydrogen production. As the loading increases from 0.1C to 0.6C, Cu 2 O / TiO 2 The hydrogen production of the photoelectrodes increased first and then decreased. Among them, the CT-1h-0.3C photoelectrode produced the largest amount of hydrogen, reaching 187 μmol L after 5 h of photoelectrocatalytic reaction. -1 cm -2 It can be seen that the increase in hydrogen production is related to Cu 2 It is worth noting that among all the photoelectrodes, CT-1h-0.3C has the highest hydrogen production yield ( Figure 6 (b)), this is because its appropriate loading effectively reduces the interfacial charge transfer resistance and improves the efficiency of photogenerated electron transfer. By measuring the photocurrent response, the pure TiO 2 and Cu 2 O / TiO 2 Photoelectrode in Cu deposition 2 O nanoparticle photoelectrochemical behavior during the process.

[0049] Figure 6 (c) shows pure TiO 2 and Cu 2 O / TiO 2 Photocurrent density-time characteristics under intermittent Xe irradiation (i.e., UV and visible light irradiation) on Ag / AgCl electrodes with a pulse time of 50 s and an open circuit voltage applied. No significant photocurrent density was observed for all samples in the dark. Obviously, the photocurrent density of all electrodes increased after light irradiation, indicating that the TiO2 substrate and Cu 2 O / TiO 2 The composite electrodes have good photoluminescence properties. In addition, compared with pure TiO 2 Photoelectrode, Cu 2 O / TiO 2 The photocurrent density of the photoelectrode increases with the Cu 2 O nanoparticle loading increases first and then decreases, indicating that Cu 2 The loading of O nanoparticles is easy to optimize. The highest stable photocurrent density (i.e. 329*10 -4 A cm -2 ; Figure 6 The red curve in (c) is generated from the 0.1C deposited sample, in which only a trace amount of Cu is formed. 2 O nanoparticles. Figure 6 (d) shows the pure TiO 2 and Cu 2 O / TiO 2EIS spectra of the electrodes. A semicircle is observed at high frequencies for all electrodes, which is due to the charge transfer resistance at the electrode / electrolyte interface. 2 O / TiO 2 The semicircle radius of the photoelectrode is smaller than that of pure TiO 2 The semicircle radius of the nanotubes indicates that the Cu 2 O is more efficient. The semicircle of the CT-1h-0.3C electrode is the smallest, indicating that the charge transfer is more efficient due to Cu 2 The optimal loading amount of O is that its charge transfer resistance is minimal.

[0050] Example 3

[0051] As a control example of Example 1, the anodizing time of 1h in step S2 was modified to 0.5h, 1.5h, 2.0h, 2.5h, 3.0h, 3.5h, 4.0h, 4.5h and 5.0h in sequence, and the other steps were the same as in Example 1; finally, the mesh Cu under different oxidation times was obtained. 2 O / TiO 2 The composite pn-type heterojunction photoelectrocatalytic materials are respectively recorded as CT-0.5h-0.3C, CT-1.5h-0.3C, CT-2.0h-0.3C, CT-2.5h-0.3C, CT-3.0h-0.3C, CT-3.5h-0.3C, CT-4.0h-0.3C, CT-4.5h-0.3C, and CT-5.0h-0.3C.

[0052] A self-made H-type electrolytic cell was used to prepare TiO 2 Nanotube arrays (TiO 2 Photoelectrode) or the mesh Cu prepared in step S4 2 O / TiO 2 Composite pn-type heterojunction photoelectrocatalytic material (Cu 2 O / TiO 2 The photoelectrode was used as the working electrode, the platinum sheet was used as the negative electrode, and the saturated silver chloride electrode was used as the reference electrode for photoelectrocatalytic hydrogen production. The hydrogen production electrolyte was 0.1 M Na 2 SO 4 Electrolyte, test the photoelectrochemical performance of different electrodes.

[0053] A self-made H-type electrolytic cell was used to prepare TiO 2 Nanotube arrays (TiO 2 Photoelectrode) or the mesh Cu prepared in step S4 2 O / TiO 2 Composite pn-type heterojunction photoelectrocatalytic material (Cu 2 O / TiO 2The photoelectrode was used as the working electrode, the platinum sheet was used as the negative electrode, and the saturated calomel electrode was used as the reference electrode for photoelectrocatalytic hydrogen production. The hydrogen production electrolyte was 0.5 M Na 2 SO 4 Electrolyte, test the photoelectrocatalytic performance of different electrodes.

[0054] Figure 7 (a)-(j) are TiO2 at different oxidation times in Examples 1 and 3, respectively. 2 SEM morphology of the photoelectrode. Figure 7 As shown in (a)-(j), when the anodization time is 0.5, 1.0 h, 1.5 h, 2.0 h, 2.5 h, 3.0 h, 3.5 h, 4.0 h, 4.5 h and 5.0 h, respectively, the prepared TiO 2 The lengths of the nanotubes are 4.99, 10.73, 15.09, 16.06, 17.96, 21.32, 30.16, 31.15, 32.01, and 35.03, respectively.

[0055] Figure 8 Cu prepared at different oxidation times in Examples 1 and 3 2 O / TiO 2 The hydrogen production of the photoelectrode (a), the Faraday efficiency of hydrogen production (b), the photocurrent response (c), and the EIS (d). As the oxidation time gradually increases, the corresponding photoelectrocatalytic hydrogen evolution activity generally increases first and then decreases ( Figure 8 (a)). CT-3.0h-0.3C has the highest hydrogen evolution yield, reaching 383 μmol cm -2 , Faraday efficiency up to 91% ( Figure 8 (b)). The reasons are as follows from the analysis of nanotube length, photocurrent response and electrochemical impedance spectroscopy: First, from 0.5 hours to 3.0 hours, the length of the nanotubes increases slowly with the extension of the anodization time; after the anodization time reaches 3.5 hours, the length of the nanotubes increases sharply, increasing by nearly 10μm in half an hour; longer nanotubes lead to larger overall cylindrical cracks, which may be an important reason why the CT-3.0h-0.3C photoelectrode has the highest hydrogen evolution yield and efficiency. Secondly, from Figure 8 As can be seen from the photocurrent response curve in (c), the photocurrent value of the CT-3.0h-0.3C photoelectrode is more than three times that of the other photoelectrodes. Figure 8 In (d), EIS also shows that the semicircle of CT-3.0h-0.3C photoelectrode is the smallest in the high-frequency part, indicating that its charge transfer resistance is the smallest. 2 O / TiO 2 -3.0h photoelectrode has the highest hydrogen evolution yield and efficiency.

[0056] Example 4

[0057] As a control example of Example 1, the working voltage 0.5V in step S4 is modified to 0.7V, 0.9V, 1.1V, 1.3V and 1.5V in sequence, and the other steps are the same as in Example 1.

[0058] A self-made H-type electrolytic cell was used to prepare TiO 2 Nanotube arrays (TiO 2 Photoelectrode) or the mesh Cu prepared in step S4 2 O / TiO 2 Composite pn-type heterojunction photoelectrocatalytic material (Cu 2 O / TiO 2 The photoelectrode was used as the working electrode, the platinum sheet was used as the negative electrode, and the saturated silver chloride electrode was used as the reference electrode for photoelectrocatalytic hydrogen production. The hydrogen production electrolyte was 0.1 M Na 2 SO 4 Electrolyte, test the photoelectrochemical performance of different electrodes.

[0059] A self-made H-type electrolytic cell was used to prepare TiO 2 Nanotube arrays (TiO 2 Photoelectrode) or the mesh Cu prepared in step S4 2 O / TiO 2 Composite pn-type heterojunction photoelectrocatalytic material (Cu 2 O / TiO 2 The photoelectrode was used as the working electrode, the platinum sheet was used as the negative electrode, and the saturated calomel electrode was used as the reference electrode for photoelectrocatalytic hydrogen production. The hydrogen production electrolyte was 0.5 M Na 2 SO 4 Electrolyte, test the photoelectrocatalytic performance of different electrodes.

[0060] Fig. 9 The Cu prepared under different applied voltages is shown 2 O / TiO 2 Hydrogen production yield of the photoelectrode (a) and Faraday efficiency of hydrogen production (b). Fig. 9 (a) shows the corresponding hydrogen production efficiency. When the applied voltage gradually increases from 0.5 V to 1.5 V, compared with SCE, Cu 2 O / TiO 2 The hydrogen production gradually increased under continuous UV-visible light irradiation. When the applied bias voltage was 1.5 V, the hydrogen production after 5 hours of reaction was 495.71 μmol L -1 cm -2 . Fig. 9(b) clearly shows the maximum hydrogen production, and the peak hydrogen production efficiency is 91.00% when an additional voltage of 1.1 V is applied. The reason is as follows: the hydrogen precipitation reaction and oxygen precipitation reaction of the photoelectrocatalytic system occur simultaneously at the working electrode and the counter electrode, respectively, and these two reactions are competitive. At an additional voltage of 1.1 V, the photoelectrochemical activity of the hydrogen evolution reaction reaches a peak and weakens the oxygen evolution reaction.

[0061] Those skilled in the art should understand that the above are only some specific embodiments of the present invention, rather than all embodiments. It should be noted that for those of ordinary skill in the art, many modifications and improvements can be made, and all modifications or improvements that do not exceed the scope of protection of the present invention should be regarded as the scope of protection of the present invention.

Claims

1. A method for preparing a network Cu2O / TiO2 composite pn-type heterojunction photoelectrocatalytic material, characterized in that: The steps include: S1. Using ethylene glycol as solvent, add pure water and ammonium fluoride in sequence, and stir evenly to prepare an anodic oxidation electrolyte; S2, using a double electrode system, with 80-100 mesh titanium mesh as anode and copper plate as cathode, applying a constant voltage for oxidation to obtain a mesh titanium dioxide nanotube array; S3, add copper sulfate pentahydrate to pure water at a concentration of 4-10 g / 200 ml, adjust the pH to 8-10, and continue stirring for 5-12 hours to obtain an alkaline copper sulfate pentahydrate electrolyte; S4. Using a three-electrode system, immerse the mesh titanium dioxide nanotube array obtained in step S2 in an alkaline copper sulfate pentahydrate electrolyte as a working electrode, soak for 5-20 minutes until the electrode environment is stable, apply a working voltage of 0.5-1.5V, and obtain a mesh Cu2O / TiO2 composite pn-type heterojunction photoelectrocatalytic material with a loading capacity of 0.1-0.6C based on the deposited charge amount displayed by the electrochemical workstation.

2. The method for preparing the network Cu2O / TiO2 composite pn-type heterojunction photoelectrocatalytic material according to claim 1, characterized in that: The volume of ethylene glycol in the electrolyte of step S1 is 1000 ml, the volume of pure water is 8.75-17.5 ml, and the mass of ammonium fluoride is 2-4 g.

3. The method for preparing the network Cu2O / TiO2 composite pn-type heterojunction photoelectrocatalytic material according to claim 2, characterized in that: The volume of ethylene glycol in the electrolyte of step S1 is 1000 ml, the volume of pure water is 17.5 ml, and the mass of ammonium fluoride is 4 g.

4. The method for preparing the network Cu2O / TiO2 composite pn-type heterojunction photoelectrocatalytic material according to claim 1, characterized in that: In step S2, a constant voltage of 10-80 V is applied, and the oxidation time is 0.5-5 h.

5. The method for preparing the network Cu2O / TiO2 composite pn-type heterojunction photoelectrocatalytic material according to claim 3 or 4, characterized in that: In step S2, a constant voltage of 60 V is applied, and the oxidation time is 1 h.

6. The method for preparing the network Cu2O / TiO2 composite pn-type heterojunction photoelectrocatalytic material according to claim 5, characterized in that: In step S3, copper sulfate pentahydrate is added to pure water at a concentration of 5 g / 200 ml.

7. The method for preparing the network Cu2O / TiO2 composite pn-type heterojunction photoelectrocatalytic material according to claim 6, characterized in that: In step S4, a working voltage of 0.5 V is applied to obtain a mesh Cu2O / TiO2 composite pn-type heterojunction photoelectrocatalytic material with a loading of 0.3C.

8. The method for preparing the network Cu2O / TiO2 composite pn-type heterojunction photoelectrocatalytic material according to claim 1, characterized in that: In step S4, the counter electrode of the three-electrode system is a platinum sheet, and the reference electrode is a saturated silver chloride electrode.

9. A network Cu2O / TiO2 composite pn-type heterojunction photoelectrocatalytic material obtained by the preparation method of a network Cu2O / TiO2 composite pn-type heterojunction photoelectrocatalytic material as described in any one of claims 1 to 8.

10. Use of a network Cu2O / TiO2 composite pn-type heterojunction photoelectrocatalytic material as claimed in claim 9 in photoelectrocatalytic production of hydrogen.

Citation Information

Cited By

  • Recyclable porous copper / cuprous oxide filamentous catalytic material and preparation method thereof

    CN120443229A